The impact of gap years on personal and career related growth - Silva, Daniel Filipe Graça da (2021)
For this Work Project, I have decided to focus on how an individual changes their perception on the impact and value of their gap year. In order to analyze this topic further, I have decided to interview individuals who have taken gap years, to extract information regarding what made them change their perception on the matter. In order to capture this information, I utilized both a narrative approach (to better understand the individual’s journey, along with their changing mindset) and a case study approach (to better understand the phenomenon of gap years, while further elaborating what could explain this change in mindset). This was ultimately accomplished through a series of in-depth interviews with college students and Human Resource department managers, in order to gain a better understanding of gap years and its impact. In this Work Project, we defined a gap year as “typically a 1-year academic break where a student reassesses their overall career goals and objectives.” The individual can still be engaged in a separate job/activity, as long as, it deviates from their formal education and planned career path. These factors served as the scope or parameters that was utilized in order to obtain information. I decided to focus on two different groups: college students who have taken a gap year who have views that evolved over time due to their work/activity related experiences, and HR departments to better understand this phenomenon and how it can impact future employment prospects for that individual over time.(All descriptive/narrative accounts of each individual’s story can be found in Appendix B section of this paper.) What I ultimately found was that gap years had a profound positive impact on an individual’s personal and career-related growth..